Profissionalização feminina em Cuiabá : uma análise das narrativas da revista A Violeta e do jornal A Cruz (1920-1930) - Arruda, Geisa Luiza de (2019)
The present research aims to analyze the narratives about female professionalization in Cuiabá inserted in the feminine magazine A Violeta and in the catholic and conservative newspaper A Cruz between 1920 and 1930. Analyzing in a qualitative way the narratives present in the two media, we present some professions performed by women, such as: domestic activities, hairdressers, public servants and teachers and how these activities were portrayed in the local press. The feminist narratives of A Violeta magazine, although contained, are compared to the conservative narratives of the newspaper A Cruz in a context that includes the republican ideals of the early twentieth century, modernism in vogue, and the Catholic Church's need to conserve conducts and behaviors considered as natural. The engagement of the magazine's writers in the defense of female professionalization as a form of emancipation presents itself as a highlight in a context in which patriarchal and clerical society dictated rules and customs. In this way, we intend to shed light on certain professions carried out by women and to analyze how narratives, especially those from the press, delineate social behaviors, naturalize actions and fix gender roles.